2013
DOI: 10.1016/j.jped.2013.02.019
|View full text |Cite
|
Sign up to set email alerts
|

Rotavirus epidemiology before and after vaccine introduction

Abstract: The study evidenced a significant decrease in the prevalence of rotavirus, mainly in children aged between 0 and 36 months in the 2007-2011 period, as well as a reduction in G1 genotype circulation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 25 publications
1
18
0
Order By: Relevance
“…In each of the three sites, the reduction in rotavirus prevalence were observed post‐vaccine introduction. These findings convincingly demonstrate the impact of vaccination in reducing the burden of severe rotavirus disease in Moroccan children, consistent with data from other studies worldwide studies [Zeller et al, ; Assis et al, ; Pendleton et al, ]. During the pre‐vaccine period, the prevalence of rotavirus hospitalizations peaked during the cooler months of September–December with a defined peak in November.…”
Section: Discussionsupporting
confidence: 91%
“…In each of the three sites, the reduction in rotavirus prevalence were observed post‐vaccine introduction. These findings convincingly demonstrate the impact of vaccination in reducing the burden of severe rotavirus disease in Moroccan children, consistent with data from other studies worldwide studies [Zeller et al, ; Assis et al, ; Pendleton et al, ]. During the pre‐vaccine period, the prevalence of rotavirus hospitalizations peaked during the cooler months of September–December with a defined peak in November.…”
Section: Discussionsupporting
confidence: 91%
“…RV is responsible for 1 in 3 cases of severe acute gastroenteritis in children less than 5 years of age hospitalized with diarrhea in urban Pakistani hospitals. The detection rate of 30.5% is lower than the estimated overall Asia burden of 37.5%, though wide variability ranging from 12% in Hong Kong to 56% in Cambodia has been reported [25] [28] . Our study showed that most cases of RV are in children under the age of 2 years (87%), similar to that described from other Asian settings.…”
Section: Discussionmentioning
confidence: 79%
“…A possible hypothesis is that the introduction of RV1 vaccine into the NIP has helped to decrease the prevalence of predominant Wa-like strains facilitating the increase of the heterotypic (DS-1-like) RVA strain G2P [4] in the Brazilian population. In addition, the long period of low or no circulation of genotype G2P [4] in Brazil previous to RV1 introduction would have created favorable conditions for the accumulation of immunological susceptible individuals (Carvalho-Costa et al, 2009;Assis et al, 2013). These facts, together with the genetic diversity found in different geographical regions throughout the years before, and after the introduction of the vaccine might explained the high prevalence of genotype G2P [4] in Brazil since 2005.…”
Section: Discussionmentioning
confidence: 99%